POLICY CHANGE INCH BY INCH: POLICY ENTREPRENEURS IN THE HOLY BASIN OF JERUSALEM. (4th August 2016) - SHPAIZMAN, ILANA; SWED, ORI; PEDAHZUR, AMI
Abstract : Facing barriers to change, policy entrepreneurs often shift their activities to a more favourable venue. In the new venue they either pressure the system from the outside, leading to policy punctuation, or make incremental changes within the existing system which over time will accumulate to a significant change in the status quo. This article aims to expand our understanding of policy entrepreneurs' role in the policy process by examining the strategies they use in the incremental path. Specifically, it focuses on one gradual change strategy, conversion – redirection of existing institutions to new purposes. Based on the case of policy entrepreneurs in the Holy Basin of Jerusalem, the findings indicate that when the entrepreneurs shift the venue to the bureaucracy they can establish cooperative relations with the government that will provide them with the needed capacities to exploit the gaps in the existing rules and redirect them to serve their aim.